Fotografi Urban Landscape Dengan Objek Hiburan Alternatif Di Yogyakarta - Astiti, Anin (Capture : Jurnal Seni Media Rekam, 2011)
Nowadays urban landscape has been in the talks of the people. Basically, urban landscapephotography is not a novelty, because it has similarity in the techniques with streetphotography. The urban landscape photography captures object and moment in thescope of a cityscape or urban life. The street photography technique is considered as asimple method to capture all that happens within an urban setting. With using alternativeentertainment as objects in the urban landscape photography, the photographer triesto express simplicity that is felt spontaneous but carry information or messages for theaudiences. Other sides of urban life in the big city have so many interesting things thatcan be expressed using photography.